Mesoporous cerium oxide for fast degradation of aryl organophosphate flame retardant triphenyl phosphate - Ederer, Jakub; Šťastný, Martin; Došek, Marek; Henych, Jiří; Janoš, Pavel (RSC advances, 2019)
Cerium oxide nanoparticles were prepared by calcination of basic cerous carbonate (as a precursor) obtained by precipitation from an aqueous solution. Prepared samples were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR), high resolution scanning electron microscopy (HRSEM), BET (Brunauer-Emmett-Teller) surface area and porosity measurement. Prepared cerium oxide was applied as a destructive sorbent for the fast and safe degradation of organophosphorus flame retardant triphenyl phosphate (TPP). It was shown that cerium dioxide was effective in the decomposition of TPP by cleavage of the P-O-aryl bond in the flame retardant molecule. A degradation mechanism for TPP on the ceria surface was proposed. The degradation is governed by conversion of TPP via diphenyl phosphate (DPP) to the final product identified as phenol (Ph). The key parameter increasing the degradation efficiency of CeO2 is the temperature of calcination. At optimum calcination temperature (500 °C), the produced ceria retains a sufficiently high surface area and attains an optimum degree of crystallinity (related to a number of crystal defects, and thus potential reactive sites). The fast and efficient degradation of organophosphorus flame retardant TPP was observed in a polar aprotic solvent (acetonitrile) that is miscible with water.